Impact of Active Learning Methods on Students' Learning and Course Results - Desai, Sandeep R. (Journal of Engineering Education Transformations, 2022)
Active involvement of the students during classroom sessions is becoming a tough task for those teaching to higher classes and upto some extent for those teaching in the schools. The reason is the change in learning styles of the students which ultimately call for the change in teaching styles too. In order, to satisfy the students in the world of competition today, the use of active and cooperative learning techniques is increased in the engineering institutes. This helps to increase the quality of technical education imparted by the institutes and help them to be distinguished due to the enhanced index of students' learning. The present study reports the application of some of the active learning techniques that include the Jigsaw technique, Muddiest point technique, Concept mapping, Case Study and Team-based learning. The different techniques are used for different segments of the 'Hydraulics and Pneumatics' course delivered to final year Automobile Engineering students studying in the final semester. The course contents, methodology of application of techniques, the students' responses and outcomes of application of the active learning techniques are discussed in the paper. It is concluded that proper planning, availability of resources and students' cooperation make it easier to apply modern-day teaching techniques. The positive change in students' learning level, their graduate attributes, passing percentage and average marks is noticed by doing the above-mentioned experiments during the classroom sessions.